Students' Learning Engagement In Contextual Teaching And Learning Strategies Management: The Voices From English Education Classroom - Sabudu, Delli (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
This study investigates how Contextual Teaching and Learning (CTL) strategies influence student engagement in higher education, particularly in a Drama Analysis classroom. Employing a qualitative design, data were collected through classroom observations, semi-structured interviews, and reflective writings. Thematic analysis identified three interrelated dimensions of engagement: behavioral, cognitive, and emotional. Findings show that CTL enhances participation, critical reflection, and empathy, yet challenges remain in managing open-ended tasks. The study underscores the pedagogical value of CTL in fostering meaningful and engaging learning experiences in higher education. The findings revealed that CTL strategies enhanced student engagement, encompassing behavioural, cognitive, and emotional aspects. Students showed increased behavioral engagement through better attendance and enthusiastic participation, while cognitive engagement was evidenced by active involvement in assignments and peer learning.  Emotional engagement also rose, leading to improved communication skills, personal growth, and empathy. However, some challenges, such as navigating open tasks, were also identified. In conclusion, the findings of this study illustrate the significant influence of CTL strategies on student engagement and learning outcomes in drama classes. Consequently, the study provides educators with practical implications for the creation of engaging and meaningful learning experiences through the utilisation of CTL strategies. In conclusion, the application of engaging and contemporary pedagogical strategies that are aligned with the specific context is essential for meaningful learning.